Pengembangan Media Pembelajaran Augmented Reality Card Berbantuan Aplikasi Assemblr Edu pada Materi Sistem Pencernaan Manusia bagi Peserta Didik Kelas XI di MAN 1 Boalemo - Daud, Pransiska Sunarti; Mardin, Herinda; Akbar, Muh. Nur; Lamondo, Djuna; Usman, Nurul Fajryani (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to describe the validity and practicality of Augmented Reality Card learning media assisted by the Assemblr Edu application on the human digestive system material for grade XI students at MAN 1 Boalemo. The method used in this study is the research and development method with the ADDIE model which includes three stages, namely analyze, design, and develop. The data collection instruments in this study consisted of a needs analysis questionnaire, interviews, media validity test sheets, material validity test sheets, and teacher and student response questionnaires. The results of the study showed that the validity of Augmented Reality Card learning media on human digestive system materials obtained a percentage of 90% of media experts with very valid criteria, and 93.3% of material experts with very valid criteria. The test of the practicality of learning media was seen through the results of the teacher response questionnaire which obtained a percentage of 95% and the student response questionnaire of 88% with very practical criteria. The assessment obtained from user responses, namely teachers and students as a whole, was 91.5% which was indicated as a practical value. Based on the results of the research, it can be concluded that Augmented Reality Card learning media assisted by the Assemblr Edu application on human digestive system materials is declared valid and practical, so it is suitable for use as a tool in learning biology, especially human digestive system materials.